PRODUKSI MAKNA HEADLINE JOKOWI-MA’RUF DALAM PILPRES 2019 DI MEDIAINDONESIA.COM (STUDI HERMENEUTIKA GADAMER) - Prakoso, Bayujati (Prosiding Seminar Nasional Berseri, 2020)
This study tried to analyze the production of meaning in headline News for Jokowi-Maâ€™ruf at the presidential election 2019 in mediaindonesia.com November 21th â€“ December 21th edition 2019 using the Gadamer hermeneutic analysis. To achieve the goal, this study used Gadamer’s hermeneutic theory for a qualitative approach, interpretive paradigm, and Gadamer’s hermeneutic method. The results of this study indicate that, firstly, the mediaindonesia.com headline is temporary, and does not provide complete information about the subject in the headline content. Secondly, headline was a form of appreciation to Jokowi in term of infrastructure development in Indonesia. Thirdly, it would have an impact in the manner of an electoral for the Jokowi in Presidential Election 2019, as the selection of news sources Jusuf Kalla (Advisory Board group 01). Fourthly, there is a tendency to construct reality efforts from the survey results in favor of group 01 by becoming a source of positive news to group 01. In addition, there are impacts arising from meaning production of headlines, namely the headline was used as a tool for political consolidation, and a means of image publication, and company financial company.